Dialogisk coaching af ledergrupper: Facilitering af fælles ledelsesmæssige udfordringer - Alrø, Helle; Dahl, Poul Nørgård (Academic Quarter | Akademisk kvarter, 2013)
This article presents and discusses a dialogic approach to coaching of leader groups. This approach is developed through an action research project and through collaboration between four leadership groups in a Danish municipality, two organization consultants and two researchers from Aalborg University in Denmark. The project aims at developing dialogic group coaching theoretically and practically while keeping a focus on learning and development in leadership practice.